1990
DOI: 10.1016/0033-5894(90)90064-r
|View full text |Cite
|
Sign up to set email alerts
|

Plant and Insect Remains from the Wisconsinan Interstadial/Stadial Transition at Wedron, North-Central Illinois

Abstract: Organic material exposed within a small swale fill in Pit 6 of the Wedron Silica Sand Co. near Wedron in LaSalle County, Illinois, includes well-preserved pollen, plant macrofossils, and insect remains. This material occurs in slackwater sediment in the lower part of the Peddicord Formation, which was deposited as existing valleys were dammed by fluvial aggradation during the initial late Wisconsinan advance of Laurentide ice into the Wedron area. Wood from the organic horizon has a radiocarbon age of 21,460 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…; Fig. 2; Baker et al, 1986Baker et al, , 1989Garry et al, 1990;Woodman et al, 1996;Schwert et al, 1997;Baker and Mason, 1999;Curry and Yansa, 2006). The presence of ice-wedge casts (Péwé, 1983;Johnson, 1990;Walters, 1994) and extensive frost-shattered colluvial and solifluction deposits (Bettis and Kemmis, 1992;Bettis, 1994;Mason and Knox, 1997) suggest the significant impact of fullglacial climates on upland and valley-margin landscapes beyond the glacial margin.…”
Section: Last-glacial Environment and Fluvial Responsementioning
confidence: 93%
“…; Fig. 2; Baker et al, 1986Baker et al, , 1989Garry et al, 1990;Woodman et al, 1996;Schwert et al, 1997;Baker and Mason, 1999;Curry and Yansa, 2006). The presence of ice-wedge casts (Péwé, 1983;Johnson, 1990;Walters, 1994) and extensive frost-shattered colluvial and solifluction deposits (Bettis and Kemmis, 1992;Bettis, 1994;Mason and Knox, 1997) suggest the significant impact of fullglacial climates on upland and valley-margin landscapes beyond the glacial margin.…”
Section: Last-glacial Environment and Fluvial Responsementioning
confidence: 93%
“…Other studies have documented plants and animals of the tundra or tundra-boreal transition zone before 11 450 yr BP in southeastern Minnesota, and as late as about 14 000 yr BP in northern and eastern Iowa, and northern Illinois (Amundson & Wright 1979;Baker et al 1997;Baker & Waln 1985;Birks 1976Birks , 1981Garry et al 1990;Holloway & Bryant 1985;Jelgersma 1962).…”
Section: Paleoecological Reconstructionsmentioning
confidence: 99%
“…The beginning of the permafrost episode has been dated by Garry et al (1990), who studied a site at Wedron, in central Illinois, and found fossil plants and insects that indicate a transition from boreal forest to tundra about 21 460 § 470 BP. Baker et al (1989) gave a date of 22 000 yr BP for the beginning in Iowa and Illinois, and Curry & Follmer (1992) gave 23 000 yr BP for several sites in northern Illinois.…”
Section: Paleoecological Reconstructionsmentioning
confidence: 99%
“…An organic deposit in a small swale fill was sampled from a sand pit at this site in north-central Illinois (Garry et al, 1990). Wood from this deposit has been dated at 21 460 ± 470 yr BP.…”
Section: Wedron Illinoismentioning
confidence: 99%